초등학교 교사의 건강지각, 건강상태와 건강증진행위 - 정수희; 김동희; Jung, Su Hui; Kim, Dong-Hee (韓國學校保健學會誌, 2017)
Purpose: The purpose of this study was to identify health promotion behaviors of elementary school teachers and investigate the factors influencing the health promotion behaviors. Methods: Data were collected from 234 elementary school teachers in the B Metropolitan City Office of Education from 5th to 30th October, 2016. The collected data were analyzed by descriptive statistics, t-test, ANOVA, $Scheff{\acute{e}}$ test, Mann-Whitney test, Kruskal-Wallis test, Spearman correlation coefficient and multiple regression analysis, using SPSS/WIN 23.0. Results: The elementary school teachers' health perception scored 2.94 out of 4, health status 1.59 out of 3, and health promotion behaviors 2.66 out of 4. The level of mental health status (1.67) was higher than that of physical health status (1.54) and the most practiced health promotion behavior was spiritual growth (3.15) and the least was health responsibility (2.00). Significant negative correlations were found between health perception and health status (r=-.59, p<.001) and between health status and health promotion behaviors (r=-.41, p<.001). A significant positive correlation was found between health perception and health promotion behaviors (r=.32, p<.001). The significant factors influencing health promotion behaviors were job stress and health status. These factors explained 19.6% of the health promotion behaviors. Conclusion: It is necessary to establish measures to increase the health perception and health promotion behaviors of elementary school teachers and improve their health status. In addition, since job stress and health status are factors influencing health promotion behaviors, it is necessary to actively manage job stress and health status in order to increase health promotion behaviors.